Representing the Ideology of Extremism in Mohsin Hamid's The Reluctant Fundamentalist: A Critical Stylistic Study (International Journal of Language, Literacy and Translation, 2025)
Extremism revolves around notions and beliefs. As such, the way text producers perceive them is affected (and even shaped) by their ideologies and background. So far, the present study deals with such a concept by selecting a post 9/11 novel. The post 9/11 literature is rich with the ideology of extremism. Nevertheless, the study is limited to Mohsin Hamid's Novel The Reluctant Fundamentalist. This novel is shaped by the Pakistani Muslim viewpoint. In order to access such an ideology about extremism, the study will be conducted according to Jeffries’s critical stylistic approach. Moreover, the study aims at discussing the linguistic and textual meanings about extremism as represented by a Muslim writer. The study concludes that the writer employs all the critical stylistic tools set by Jeffries. As a Muslim writer, Hamid reinforces the idea of the suffering of Muslims after 9/11 attacks.